HYPOCHOLESTEROLAEMIC EFFECT OF LEAF PROTEIN CONCENTRATE (LPC) ON BLOOD CHOLESTEROL OF RATS AND POULTRY - Ali, Sakhawat; Firdos, Tahira; Shah, WH; Shah, F H (Biological Sciences - PJSIR, 2002)
Leaf protein concentrate (LPC) was extracted from barseem leaves and incorporated in the diet replacing casein in case of rats and fishmeal in poultry. A series of experiments were cond ucted on rats and poultry to determine the hypocholesterolaemic effect of LPC on the blood cholesterol of rats and poultry. Results indicated that incorporation of LPC decreased cholesterol level of blood in rats and poultry. Decrease in phospholipids has also been noticed with the increase in concentration of LPC. Decrease in cholesterol content in eggs laid by hens fed on diet containing LPC has also been observed.